Concise Review: Developing Best‐Practice Models for the Therapeutic Use of Extracellular Vesicles. (17th July 2017) - Reiner, Agnes T.; Witwer, Kenneth W.; van Balkom, Bas W.M.; de Beer, Joel; Brodie, Chaya; Corteling, Randolph L.; Gabrielsson, Susanne; Gimona, Mario; Ibrahim, Ahmed G.; de Kleijn, Dominique; Lai, Charles P.; Lötvall, Jan; et al.
Abstract: Growing interest in extracellular vesicles (EVs, including exosomes and microvesicles) as therapeutic entities, particularly in stem cell‐related approaches, has underlined the need for standardization and coordination of development efforts. Members of the International Society for Extracellular Vesicles and the Society for Clinical Research and Translation of Extracellular Vesicles Singapore convened a Workshop on this topic to discuss the opportunities and challenges associated with development of EV‐based therapeutics at the preclinical and clinical levels. This review outlines topic‐specific action items that, if addressed, will enhance the development of best‐practice models for EV therapies. Stem Cells Translational Medicine 2017;6:1730–1739 Abstract : In this concise review, members of the International Society for Extracellular Vesicles (ISEV) and the Society for Clinical Research and Translation of Extracellular Vesicles Singapore (SOCRATES) discuss opportunities and challenges in development of EV or exosome‐based therapeutics at the preclinical level, ranging from efficacy and quality control tests to determining mechanisms of action, and in translation.